A distinct exclamative clause type would require an illocutionary force distinct from assertion, question, and command. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
A distinct exclamative clause type would require an illocutionary force distinct from assertion, question, and command.
iso-id: iso:argument:gxm0eYbL; sha256: sha256:a5ce132db31ba57fe095a44849c2839fbcfb2d13642dd0fe954db8c3aaba4bf4